Social competence of nurses in hospital: A scoping review - Aditya Teguh Widodo; Ni Gusti Ayu Eka; Enjelika Putri Manalu; Erica Dorelia Pajuk; Kyela Friska br Sinurat (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Social competence plays an important role in nursing care. Nurses who have good social competence can provide more humane and empathetic care, which can improve patient satisfaction and health outcomes. However, in the last five years, there has been an increasing trend of patient complaints in hospitals related to the social competence of nurses. Purpose: To map social competence of nurses in hospitals settings. Method: The review followed the Joanna Briggs Institute (JBI) Reviewers’ Manual. Three electronic database searches conducted in PubMed, MEDLINE with full text (EBSCO), and ScienceDirect (Elsevier). Studies selected based on inclusion and exclusion criteria, and data synthesized using descriptive statistics and narrative summaries of both qualitative and quantitative findings. The eligible population includes nurses who provide direct patient patients care. The concept of the study focuses on social competence and the context is hospital settings. This review considered qualitative, quantitative, and mixed-method studies published between 2021 and 2025. The protocol registered in the Open Science Framework (OSF). Results: The primary focus across studies was on aspects of social competence in nursing, including communication, empathy, cultural competence, interpersonal relationships, and professional behavior in hospital settings. Conclusion: This scoping review analyzed 12 studies (2021–2025) and found that nurses’ social competence—covering communication, empathy, cultural sensitivity, and interpersonal skills—is a learnable and essential aspect of nursing that enhances patient care and teamwork. The review emphasizes the need for structured training, organizational support, and further research to strengthen social competence in nursing practice.